2003
DOI: 10.1021/ol035977y
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Ionic Liquids as Soluble Supports for Organic Synthesis. Demonstration with a Suzuki Coupling Reaction

Abstract: The efficiency of ionic liquid supported synthesis was demonstrated by the Suzuki reaction of ionic liquid supported iodobenzoate compounds with arylboronic acids in aqueous media to give, after cleavage with ammonia/methanol, biaryl products in good yields and high purities, without the need for chromatographic purification. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…[8a,20] The 1-(2-hydroxyethyl)-3-methylimidazolium tetrafluoroborate and starting substrate 15 were synthesized as published. [21,22] Dimethyl malonate, BSA [N,O-bis(trimethylsilyl)acetamide] and sodium p-toluenesulfinate were commercially available. [PdA C H T U N G T R E N N U N G (allyl)Cl] 2 , [22] [acacRh(CO) 2 ] [23] and [RhA C H T U N G T R E N N U N G (COD) 2 ]BF 4 [24] on the H 3 PW 12 O 40 / SiO 2 support [11a,f] were synthesized using literature procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[8a,20] The 1-(2-hydroxyethyl)-3-methylimidazolium tetrafluoroborate and starting substrate 15 were synthesized as published. [21,22] Dimethyl malonate, BSA [N,O-bis(trimethylsilyl)acetamide] and sodium p-toluenesulfinate were commercially available. [PdA C H T U N G T R E N N U N G (allyl)Cl] 2 , [22] [acacRh(CO) 2 ] [23] and [RhA C H T U N G T R E N N U N G (COD) 2 ]BF 4 [24] on the H 3 PW 12 O 40 / SiO 2 support [11a,f] were synthesized using literature procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[42] The anchoring of RTILs to substrates may be an attractive alternative for synthetic purposes, as it may facilitate the workup and purification of products, as well as the recovery of nontransformed substrates. Recently, the kinetic resolution of (R,S)-ibuprofen catalyzed by the lipase from Candida antarctica was carried out by first anchoring this substrate to the ionic liquid [BMIM] [PF 6 ] to form IL ibuprofen esters.…”
Section: Substrate-rtil Anchoring In Biotransformationsmentioning
confidence: 99%
“…Therefore, the sequence reactions can be repeated to give more complex compounds. So far, several research groups have already demonstrated the feasibility of IL-tagged organic synthesis for small molecules (Anjaiah, Chandrasekhar, & Gree, 2004;FragaDubreuil & Bazureau, 2003;Legeay, Vanden Eynde, & Bazureau, 2005;Miao & Chan, 2003) and peptides (He & Chan, 2007;Miao & Chan, 2005). Recently, ionic liquid-tagged synthesis of oligonucleotides and oligosaccharide has also been successfully developed (Donga, Khaliq-Uz-Zaman, Chan, & Damha, 2006;He & Chan, 2006;Miao & Chan, 2006;Huang, Lei, & Wang, 2006;Pathak, Yerneni, Young, & Pathak, 2008;Yerneni, Pathak, & Pathak, 2009).…”
Section: Introductionmentioning
confidence: 99%